Розробка інформаційних систем та програмних рішень в системах обслуговування з використанням хмарних технологій - Мацюцький, В. Р. (ХНУРЕ, 2024)
This report delves into the necessity of integrating cloud technologies for developing information systems in food establishments, meeting consumer demands for convenience. In an era of rapid technological advancement, cloud adoption becomes imperative, offering flexibility and accessibility to optimize processes and reduce operational costs. Challenges like security concerns, internet stability, and potential privacy issues require proactive resolution for the stability and success of cloud solutions in the food industry. The report concludes by highlighting ongoing research, legislative adherence, and the importance of comprehensive privacy policies in cloud implementation for food establishments.
Keywords: хмарні сервіси; масштабованість додатків; управління даними; інтеграція API; безпека інформації